Two Byzantine Seals from the Excavation of the Medieval Fortress “Malkoto kale” (Yambol Region, Bulgaria) - Kanev, Nikolay (Studia Ceranea, 2022)
The present article aims to put into scholarly circulation two new unpublished Byzantine lead seals from the medieval fortress in the area of the village of Voden (municipality of Bolyarovo, Yambol region, Bulgaria). They were handed to the Regional Historical Museum in the town of Yambol as a result of the regular archaeological excavations of the site near the village of Voden, conducted in the period 2012–2019. The first seal dates from the last quarter of the 11th century and has a bust of the Holy Virgin with a halo and a round medallion with the image of the Infant Jesus Christ who blesses with both hands. From the legend on the reverse, it is clear that the bulla belonged to a Byzantine dignitary named Michael Tzitas, who advertises himself with the title of (proto)kouropalates and the position of doux. The second seal dates from the end of the 11th – the beginning of the 12th century and has an interesting and relatively rare iconographic plot depicting three military saints on the obverse, and an invocation to them on the reverse. The seal belongs to a clergyman – a metropolitan bishop of Athens, named Nicetas (Νικήτας).